Magnetic quantum oscillations in the charge-density-wave state of the organic metals a-(BEDT-TTF)2MHg(SCN)4 with M = K and Tl: Магнитоквантовые осцилляции - Kartsovnik, M.V.; Zverev, V.N.; Andres, D.; Biberacher, W.; Helm, T.; Grigoriev, P.D.; Ramazashvili, R.; Kushch, N.D.; Müller, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The low-temperature charge-density-wave (CDW) state in the layered organic metals α-(BEDT-TTF)2MHg(SCN)4 has been studied by means of the Shubnikov–de Haas and de Haas–van Alphen effects. In addition to the dominant α-frequency, which is also observed in the normal state, both the magnetoresistance and magnetic torque possess a slowly oscillating component. These slow oscillations provide a firm evidence for the CDW-induced reconstruction of the original cylindrical Fermi surface. The α-oscillations of the interlayer magnetoresistance exhibit an anoma-lous phase inversion in the CDW state, whereas the de Haas–van Alphen signal maintains the normal phase. We argue that the anomaly may be attributed to the magnetic-breakdown origin of the α-oscillations in the CDW state. A theoretical model illustrating the possibility of a phase inversion in the oscillating interlayer conductivity in the presence of a spatially fluctuating magnetic breakdown gap is proposed.